Father presence and resilience of Chinese adolescents in middle school: Psychological security and learning failure as mediators - Wei, Xueyan; Zhuang, Miao; Xue, Linfang (Frontiers in Psychology, 2023)
Introduction This study aimed to explore the association between father presence and adolescent resilience and the mediating role of psychological security and learning failure. Examining the mediating effects of learning failure and the chain mediating effect of psychological security and learning failure elucidated the link between father presence and adolescent resilience. Methods The present study conducted a questionnaire survey among Chinese middle school students on father presence, resilience, psychological security, and learning failure. The survey collected 626 valid responses. Results The findings showed that father presence, psychological security, learning failure, and resilience were significantly positively correlated; father presence had a direct effect on adolescent resilience, and psychological security and learning failure both mediated the relationship between father presence and adolescent resilience; psychological security and learning failure served as chain mediators between father presence and adolescent resilience. Discussion This study aimed to provide theoretical and practical insights into the field of family education.